Anthranilate Synthetase, an Enzyme Specified by the Tryptophan Operon of Escherichia coli: Comparative Studies on the Complex and the Subunits - Ito, Junetsu (1969)
The properties of the anthranilate synthetase complex and its separated subunits were compared in catalyzing the anthranilate synthetase reaction, chorismate + l-glutamine or NH(4)(+) → anthranilate, and the transferase reaction, anthranilate + 5′-phosphorylribosyl-1-pyrophosphate → phosphoribosyl anthranilate. It is shown that anthranilate synthetase component I is activated by normal anthranilate synthetase component II, a component II(CRM) (CRM = immunologically cross-reacting material), and by a presumed fragment of component II produced by a deletion mutant. Significant differences between the complex and its subunits are demonstrated with respect to substrate affinity, thermostability, feedback inhibitor sensitivity, and activity in the presence of various divalent cations. Of particular interest are the findings that the transferase activity of component II is only inhibitable by l-tryptophan when the component is in the complex and that this inhibition does not appear to depend upon the feedback-sensitive site of component I.